Classroom Psychomotor Education Programme to Enhance Executive Functions: A Cluster Randomised Feasibility Trial - Vassiliki Riga; Aimilia Rouvali (Youth, 2023)
An increase in children exhibiting attention difficulties has created the need for more classroom-based intervention programmes. A promising link between physical education and improvement in executive functioning has been at the centre of attention. POTENTIAL constitutes a novel classroom-based psychomotor education programme to enhance students’ attention and listening skills by improving executive functions. A cluster randomised feasibility study was conducted to explore the feasibility of a definitive trial to assess POTENTIAL’s effectiveness regarding (i) recruitment and sampling procedures; (ii) compliance and fidelity; (iii) the acceptability of POTENTIAL by teachers and children; and (iv) the appropriateness of the outcome measures. Four early years classes with an inclusion unit participated: two implemented POTENTIAL and two received no intervention. Eight children in each class (n = 32) were sampled to investigate the appropriateness of the outcome measures. Teachers’ diaries were utilised to explore the acceptability of the activities and the fidelity and compliance to the implementation. The findings regarding POTENTIAL’s acceptability were positive. The recruitment targets were met, and compliance and fidelity were good. Mixed results were produced about the appropriateness of the outcome measures. Thus, the trial protocol could be scaled up in a definitive trial. This study highlights the need for more physical education programmes to support children’s executive functioning.